2016
DOI: 10.5194/gmd-9-1-2016
|View full text |Cite
|
Sign up to set email alerts
|

Integration of nitrogen dynamics into the Noah-MP land surface model v1.1 for climate and environmental predictions

Abstract: Abstract. Climate and terrestrial biosphere models consider nitrogen an important factor in limiting plant carbon uptake, while operational environmental models view nitrogen as the leading pollutant causing eutrophication in water bodies. The community Noah land surface model with multiparameterization options (Noah-MP) is unique in that it is the next-generation land surface model for the Weather Research and Forecasting meteorological model and for the operational weather/climate models in the National Cent… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
48
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(48 citation statements)
references
References 37 publications
0
48
0
Order By: Relevance
“…It has been proposed that wood density may be a useful proxy for drought tolerance in tropical tree species (Fearnside, 1997) and that it is negatively correlated with the precipitation gradient that exists across the Amazon basin (Baker et al, 2004;but see also Ter Steege et al, 2006). Moreover, in a pan-tropical synthesis of moist tropical forest species, a weak but significant negative relationship between p o and wood density was found (Christoffersen et al, 2016). Other observational studies have found that variation in stem economic traits, such as wood density, is largely independent of hydraulic traits (Baraloto et al, 2010;Mar echaux et al, 2015).…”
Section: Introductionmentioning
confidence: 83%
“…It has been proposed that wood density may be a useful proxy for drought tolerance in tropical tree species (Fearnside, 1997) and that it is negatively correlated with the precipitation gradient that exists across the Amazon basin (Baker et al, 2004;but see also Ter Steege et al, 2006). Moreover, in a pan-tropical synthesis of moist tropical forest species, a weak but significant negative relationship between p o and wood density was found (Christoffersen et al, 2016). Other observational studies have found that variation in stem economic traits, such as wood density, is largely independent of hydraulic traits (Baraloto et al, 2010;Mar echaux et al, 2015).…”
Section: Introductionmentioning
confidence: 83%
“…FUN2.0 (Brzostek et al, 2014) included two main improvements: (i) integrated trade-offs between ECM, AM, and nonmycorrhizal roots in their C costs of N acquisition and (ii) a resistance network to allow simultaneous uptake across all pathways (Fig. At extremely high levels of soil N (i.e., at the level of fertilized agricultural fields), passive and nonmycorrhizal root uptake dominates (Cai et al, 2015). In FUN2.0, when soil N is relatively abundant, plants supporting AM have the lowest C costs; when soil N is limiting, plants supporting ECM have the most optimal strategy.…”
Section: Model Descriptionmentioning
confidence: 99%
“…Two major directions for the LSM developments include improving the existing process representations and coupling new modules and functionalities [e.g., Cai et al ., ]. For example, vegetation dynamics, detailed hydrologic processes, snowpack evolution, and biogeochemical processes have been incorporated into the Noah model [ Cai et al ., ; K. Yang et al ., ]. With these rapid developments, LSMs are capable of quantitatively evaluating the contributions of different environmental factors to the changes in runoff and projecting the hydrological changes when coupled with the outputs of a general circulation model (GCM).…”
Section: Introductionmentioning
confidence: 99%